Development of the Trying New Foods Scale: A preschooler self-assessment of willingness to try new foods. (1st September 2018) - Johnson, Susan L.; Moding, Kameron J.; Maloney, Katheryn; Bellows, Laura L.
Abstract: Food neophobia, or reluctance to try new foods, emerges typically in early childhood and can impact child food acceptance and dietary quality. Measures of child neophobia have largely been developed from an adult point of view and the items focusing on fear and disgust were created from observations of children's behaviors or from adult assumptions regarding the source of children's reluctance to try new foods. Using group interviews with 3-5-y-old children (n = 229) we investigated what the experience of being asked trying new foods is like for preschoolers. From their answers, we crafted a new assessment, The Trying New Foods Scale, designed to ask children about their self-competence to try new foods. Next, we measured preschoolers' responses (n = 233; 3–5 years of age; 107 boys, 126 girls) to these items and observed their willingness to taste 7 novel foods and their affective ratings of the foods as measures of criterion validity. A principal components analysis (PCA) revealed a single 9-item component for the Trying New Foods Scale (mean ± s.d. = 3.08 ± 0.70; α = 0.88). Children's Trying New Foods Scale score positively correlated with their willingness to try foods ratio (r = 0.21, p = .001). Initial findings indicate that the Trying New Foods Scale for preschoolers has good psychometric characteristics, including preliminary evidence of criterion validity. Children who perceived themselves as more willing to try foods actually performed the behavior of trying more foods and rated the foods more favorably than children who reported lower self-competence to try foods. Understanding neophobia from the perspective of the young child, and their perceptions of self-competence related to trying new foods, may facilitate our ability to evaluate young children's food acceptance patterns. Highlights: Assessment of neophobia has seldom asked children, themselves, about their willingness to try foods. When trying new foods, children report fear of bad taste or illness, sadness and disgust and limited positive experiences. Children who reported higher self-competence to try foods rated more foods as liked and fewer foods as disliked. Young children can assess their self-competence and willingness to try new foods.